2007
DOI: 10.1111/j.1365-2958.2006.05577.x
|View full text |Cite
|
Sign up to set email alerts
|

A PerR‐regulated metal transporter (PmtA) is an interface between oxidative stress and metal homeostasis inStreptococcus pyogenes

Abstract: SummaryIn Streptococcus pyogenes, mutation of the peroxide sensor PerR results in avirulence despite producing hyper-resistance to peroxide stress. To understand the basis of this effect, global transcription profiling was conducted revealing one highly downregulated gene (czcD), and five highly upregulated genes in the mutant. Of the latter, only pmtA contained a binding site for PerR, while phtY, phtD, lsp and rpsN2 harboured an AdcR motif and were regulated by AdcR, a repressor of an ABC-type metal transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
131
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(144 citation statements)
references
References 60 publications
13
131
0
Order By: Relevance
“…Scenarios in concordance with this hypothesis have been reported during zinc starvation for ribosomal proteins of B. subtilis and Streptococcus pyogenes (Brenot et al, 2007;Makarova et al, 2001). In accordance with this, our results showed that expression of ssu1352 ORF in the adcR-knockout strain, encoding ribosomal protein S14, is approximately 100-fold higher than in the wild-type strain (Fig.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Scenarios in concordance with this hypothesis have been reported during zinc starvation for ribosomal proteins of B. subtilis and Streptococcus pyogenes (Brenot et al, 2007;Makarova et al, 2001). In accordance with this, our results showed that expression of ssu1352 ORF in the adcR-knockout strain, encoding ribosomal protein S14, is approximately 100-fold higher than in the wild-type strain (Fig.…”
Section: Resultssupporting
confidence: 63%
“…Furthermore, Pht proteins are involved in the host-cellpathogen interaction, and it has been hypothesized that they have evolved to become sensitive to AdcR regulation in order to exploit zinc as a compartment-specific regulatory cue (Brenot et al, 2007). It is also noteworthy that Pht proteins present hydrophobic leader sequences, which presumably target these proteins to the bacterial cell surface and induce specific antibodies against pneumococcal sepsis, suggesting that Pht proteins could serve as effective vaccines against streptococcal infections (Adamou et al, 2001;Kunitomo et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Binding of AdcR, induced under conditions of high Zn 2+ concentration, inhibits the transcription of the genes under its dependence. Upon direct or indirect zinc starvation conditions, and hence a reduced intracellular concentration of this metal, repression by AdcR is relieved (Brenot et al, 2007;Claverys, 2001). However, and in contrast to what we have observed here, it was recently shown that the addition of zinc in culture medium elicits Pht production (Ogunniyi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In Bacillus subtilis, PerR regulates itself (30) and other genes, including those involved in oxidative stress defense (katA, ahpCF, mrgA) (10,14), metal homeostasis (zosA, fur, hemAXCDBL) (14,30,31), and surfactant production (srfA) (41), in response to peroxide exposure. As with OxyR, PerR homologs in other organisms tend to regulate similar classes of genes (7,8,36,48,79,91,117).…”
Section: Perrmentioning
confidence: 99%